Extension and Outreach: Not a Question of If, but How - James R. Lindner; David Dolly (Journal of International Agricultural and Extension Education, 2012)
In this article, the authors develop a conceptual framework for effective extension and outreach. Based on both our experiences and research and those of leading scholars and practitioners in the field, we offer the following ten ideas for thought, debate, discussion, and implementation. Effective extension systems must: be institutionalized, well-defined, and well-funded; address important/contemporary issues/problems; be sufficiently nimble and flexible in order to address emerging issues; be a credible and unbiased source for information/education and solutions/research; understand the needs of its customers; embrace participatory and integrated approaches; recognize that little happens in isolation and create regional/global sustainable partnership/linkages with governments, NGOs, researchers and educators; be excellent stewards of resources acquired; recognize that return on investment (ROI) from its research and outreach must be well-documented; and allow for decentralized decision-making and action when warranted.
Keywords: Extension Systems; Advisory Services; Managing Change; Perspectives; Marketing